Molecular mechanism of action of the glucocorticoid receptor:Role of ligand-dependent receptor phosphorylation and half-life in determination of ligand-specific transcriptional activity. : Contents Pages - Avenant, Chanel (Department of Molecular and Cell Biology, 2014)
Glucocorticoids mediate their effects by binding to the glucocorticoid receptor (GR), resulting in modulation of transcription of target genes via direct binding to DNA or tethering via proteinprotein interactions. A central question is what determines the rank order of ligand-selective transcription with different GR ligands for the same gene in the same cell. Using a panel of twelve GR ligands, including agonists, partial agonists and antagonists, the relationship between the extent of GR phosphorylation at S226, GR turnover and transcriptional response, was investigated using a variety of biochemical approaches. Using a phospho-S226-specific GR antibody, ligand-selective S226 phosphorylation was shown to occur in both COS-1 and U2OS cells, while GR phosphorylation at S226 was shown to inhibit maximal transactivation and transrepression efficacy. Attempts to identify the kinases responsible for this interaction were inconclusive but suggested a combination of kinases is responsible for the in vivo phosphorylation of the hGR in these cells. Similarly the rate of GR degradation was different for the different ligands. Interestingly, both ligand-selective GR phosphorylation and half-life were found to correlate with efficacy for transactivation and transrepression of model synthetic reporter genes, where agonists resulted in the greatest extent of phosphorylation and the fastest vii rate of GR turnover, suggesting a link between these functions. Furthermore experiments where transcription was blocked suggest that GR turnover does not require transcription. However, using a S226A GR mutant, as well as in experiments where GR turnover was blocked, it was established that neither phosphorylation of the GR at S226 nor GR degradation rate determines the rank order of ligand-selective GR transactivation. The mechanisms whereby GR phosphorylation influence GR-mediated transcription was further investigated using a triple phosphorylation deficient mutant. It was shown that phosphorylation at one or more of residues S203/S211/S226 is required for transactivation of a MMTV promoter but does not affect unliganded or agonist-induced GR degradation and acetylation. Additionally, it was shown that phosphorylation at S203/S211/S226 is not the sole determinant of co-activator p300 recruitment to the GR. Interestingly, GR-mediated transrepression via AP-1 is less sensitive to GR phosphorylation than GR-mediated transactivation, indicating different mechanisms in the role of GR phosphorylation on transactivation vs. transrepression. Pull-down and chromatin immunoprecipitation assays showed that phosphorylation of the GR at one or more of these residues are required for interaction of the GR with the co-activator GRIP-1 in vitro and for maximal recruitment of GR and GRIP-1 to the MMTV promoter in intact cells. Cellular fractionation showed that phosphorylation at these residues is not however required for GR nuclear localisation. Taken together these results support the conclusion that phosphorylation at one or more of S203/S211/S226 of the hGR is required for maximal transactivation response to enable GRIP-1 recruitment to the hGR.